Analysis of Vulnerable Area for Emergency Medical Services in Flood situation by using Geographic Information System - Lee, Yoon-Ha; Seo, Hyun-Cheol; Hong, Won-Hwa; Lee, Ji-Soo (International Journal of Engineering and Technology, 2018)
The influence of flooding on public health can be extremely serious. In some floods, it has been reported that the number of casualties that occurred from waterborne and water-related diseases or injuries is higher than that of drowning. Moreover, urbanization and population concentration means that more people will be exposed to flooding. Accordingly, the importance of emergency medical services for saving lives is continuously growing.In this study, regions vulnerable to emergency medical services were suggested for Seoul, the capital city of South Korea, through analysis of the service areas of emergency medical facilities. Seoul, the capital city of South Korea, was selected as the study target region, and GIS network analysis was conducted based on the location and attributed information of 52 medical centers in Seoul which were designated as hospitals capable of providing emergency medical services. As this study is a basic study on the analysis of regions vulnerable to emergency medical services in the event of a flood caused by severe rainfall, it is expected that the results of this study will contribute to decision making that aims to minimize human injuries and improve resilience in the event of a future flood.Â Â Â